Low plasma magnesium is associated with impaired brain metabolism in neonates with hypoxic‐ischaemic encephalopathy. (18th July 2016) - Chakkarapani, Elavazhagan; Chau, Vann; Poskitt, Kenneth J.; Synnes, Anne; Kwan, Eddie; Roland, Elke; Miller, Steven P.
Abstract: Aim: To determine the association between lowest plasma magnesium concentration and brain metabolism, and whether magnetic resonance imaging brain injury patterns moderated the association in hypoxic‐ischemic encephalopathy. Methods: In 131 early (day‐of‐life 3) and 65 late (day‐of‐life 10) scans of term encephalopathic infants born between 2004 and 2012, we examined the association of lowest plasma magnesium (until day‐of‐life 3) on basal ganglia and white matter peak metabolite ratios on magnetic resonance spectroscopy independent of covariates, stratified by the predominant patterns of injury (normal, basal nuclei/total, watershed, multifocal) using multiple linear regression. Results: Lowest plasma magnesium was associated with lower white matter N ‐acetyl‐aspartate/choline in the multifocal pattern on early scan (regression‐coefficient, β : 0.13; 95% CI: 0.04, 0.22) and in the basal nuclei/total pattern on late scan ( β : 0.08; 95% CI: 0.02, 0.15), and was negatively associated with basal ganglia lactate/ N ‐acetyl‐aspartate ( β : −0.16; 95% CI: −0.05, −0.28) and lactate/choline ( β : −0.1; 95% CI: −0.03, −0.17) ratio in the basal nuclei/total pattern on late scan independent of hypomagnesaemia correction, cooling and postmenstrual age at scan. Lowest plasma magnesium was not associated with metabolite ratios in other brain injury patterns. Conclusion: In infants with hypoxic‐ischaemic encephalopathy, predominant patterns of brain injury moderated the association between lowest plasma magnesium in the first three days of life and impaired brain metabolism.